Pembinaan Kidung Kawitan Wargasari Bagi Generasi Muda di Desa Batukandik Kecamatan Nusa Penida Kabupaten Klungkung - Wicaksandita, I Dewa Ketut; Wicaksana, I Dewa Ketut; Adhisantika, Sang Nyoman Gede (Pusat Penerbitan LP2MPP ISI Bali, 2025)
This community service program aims to develop the ability of young generations in Batukandik Village to sing Kidung while preserving this traditional chant as an essential part of cultural and religious ceremonies. The partner representatives, including the traditional village head and local government officials, faced challenges due to a lack of instructors and the need for young people to acquire Kidung singing skills to enrich local customary and cultural practices. A participatory approach with a structured training method was implemented to effectively transfer knowledge. This method was chosen based on an initial assessment that indicated high enthusiasm among participants and strong support from the community and village authorities. The program consisted of several phases, including community outreach and eight intensive training sessions held from August 15 to 24, 2016, with 11 participants (8 females and 3 males). The training was structured as follows: 1) Introduction to Kidung Kawitan Wargasari, focusing on practical applications, tempo, and vocal tone; 2) Hands-on vocal practice, where participants repeatedly sang Kidung Kawitan Wargasari verse by verse according to the training schedule and measurable targets; 3) Evaluation and final performance, where participants showcased their progress in a mini recital. This program had a positive impact and received appreciation from both the community and village authorities. It successfully provided participants with knowledge of Kidung and increased their interest in singing it, contributing to the preservation and strengthening of cultural values both in theory and practice within Batukandik Village.